(3GdeNJdas - (3GdMdj, CHh efUhQ, GHf GdeWgQ, LeGd GdOjf, GdMSf Hf jhSa Hf Ydj GHf GdeWgQ, J (B726(3g`s ((3CHh YHO Gddg eMeO Hf Jbj GdOjf GdMSjfjs)
(3ChdgG (B:s
(3GdMeO ddg eMb GdMb heXgQg (B... (3aEfj deG hbaJ Ydi cJH CUMGHfG GdeJbOejf hebGdGJ YdeGFfG GdSGHbjf aj Gdabg hLOJ Hjfge NdGaG aj eSGFd cKjQI eJYOOI heWGdH YXjeI eJHOOI aCMHHJ EjQGO Jdc GdeSGFd aj OSJhQ jMJhj (B...s
(3BNQgG (B:s
... (3aEfeG HMce Gddg GSJNa hYdjfG QO hGdQGO YdjfG QGO Ydi Gddg hgh Ydi MO GdTQcW HGddg YR hLd hZjQ Pdc ef GdCMGOjK GdOGdI Ydi JShjZ GdMce ddabgGA hgh YGe aj EbGeI GdMOhO hZjQgG hGdYLH Cf GHf EOQjS jOYj GdELeGY (B... (3JeJ YHGOGJ cJGH GdeNJdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, ddRQcdj (B2/ 227s
(3GdPQjYI (B20/2666s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis